2020
DOI: 10.1186/s12909-020-02031-6
|View full text |Cite
|
Sign up to set email alerts
|

Selecting top candidates for medical school selection interviews- a non-compensatory approach

Abstract: Background: Medical schools apply a range of selection methods to ensure that admitted students succeed in the program. In Australia, selection tools typically include measures of academic achievement (e.g. the Australian Tertiary Admission Rank -ATAR) and aptitude tests (e.g. the Undergraduate Medicine and Health Sciences Admissions Test -UMAT). These are most commonly used to determine which applicants are invited for additional selection processes, such as interviews. However, no previous study has examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this context, it is important to note that medical entrance tests and GPA scores may favour particular groups above others. Male gender, younger age, English as a primary language and higher socioeconomic status are all associated with higher performance in the GAMSAT [ 26 , 27 ], resulting in an overrepresentation of these students in medical programs [ 28 ]. Further, students with a Health-related background degree have been reported to achieve lower GAMSAT scores than students from other backgrounds, with Biomedical and Science students having the highest scores [ 26 ], a finding consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is important to note that medical entrance tests and GPA scores may favour particular groups above others. Male gender, younger age, English as a primary language and higher socioeconomic status are all associated with higher performance in the GAMSAT [ 26 , 27 ], resulting in an overrepresentation of these students in medical programs [ 28 ]. Further, students with a Health-related background degree have been reported to achieve lower GAMSAT scores than students from other backgrounds, with Biomedical and Science students having the highest scores [ 26 ], a finding consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the new selection process algorithm plays a key role in its superiority. A recent study that modeled a non-compensatory model for the selection of applicants to interview for medicine at UNSW demonstrated that a non-compensatory model raises the selection threshold for both ATAR and UMAT without significantly impacting the mean socioeconomic status score of the selected group (Table 4) [9]. In practice, the new selection process is more likely to de-select applicants who ranked low on one selection tool despite being ranked highly on the other 2 tools.…”
Section: Discussionmentioning
confidence: 99%
“…The new selection process's algorithm utilizes a non-compensatory approach [9], whereby performance in each of the 3 selection tools is ranked and the lowest rank among the 3 tools, including within the interview, takes priority for establishing the final selection rank. Thus, a high rank in one tool (e.g., UAC Rank) cannot compensate for a lower rank in another (e.g., interview).…”
Section: Introduction Background/rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need to evaluate the effectiveness of admission tools against a broad range of outcomes within and beyond the medical program [46]. Our review provided useful examples of selection tools for the measurement of students' different aptitudes by testing innate aptitudes disclosing suitability for a competent career in surgery.…”
Section: Clinical Implication and Future Directionmentioning
confidence: 99%